C-type natriuretic peptide preserves central neurological function by maintaining blood-brain barrier integrity - Perez-Ternero, Cristina; Pallier, Patrick N.; Tremoleda, Jordi L.; Delogu, Alessio; Fernandes, Cathy; Michael-Titus, Adina T.; Hobbs, Adrian J. (Frontiers in Molecular Neuroscience, 2022)
C-type natriuretic peptide (CNP) is highly expressed in the central nervous system (CNS) and key to neuronal development; however, a broader role for CNP in the CNS remains unclear. To address this deficit, we investigated behavioral, sensory and motor abnormalities and blood-brain barrier (BBB) integrity in a unique mouse model with inducible, global deletion of CNP (gbCNP–/–). gbCNP–/– mice and wild-type littermates at 12 (young adult) and 65 (aged) weeks of age were investigated for changes in gait and motor coordination (CatWalk™ and rotarod tests), anxiety-like behavior (open field and elevated zero maze tests), and motor and sensory function (modified neurological severity score [mNSS] and primary SHIRPA screen). Vascular permeability was assessed in vivo (Miles assay) with complementary in vitro studies conducted in primary murine brain endothelial cells. Young adult gbCNP–/– mice had normal gait but reduced motor coordination, increased locomotor activity in the open field and elevated zero maze, and had a higher mNSS score. Aged gbCNP–/– animals developed recurrent spontaneous seizures and had impaired gait and wide-ranging motor and sensory dysfunction. Young adult and aged gbCNP–/– mice exhibited increased BBB permeability, which was partially restored in vitro by CNP administration. Cultured brain endothelial cells from gbCNP–/– mice had an abnormal ZO-1 protein distribution. These data suggest that lack of CNP in the CNS impairs tight junction protein arrangement and increases BBB permeability, which is associated with changes in locomotor activity, motor coordination and late-onset seizures.